Occurrence of Salmonella and Shigella Species on Meat Contact Surfaces of Selected Butcher Shops in Wukari Metropolis, North-Eastern, Nigeria - C, Hammuel; J, Briska (Darul Yasin Al Sys, 2024)
Bacterial contamination of meat occurs in different stages ranging from surfaces of slaughter house, during transportation and surfaces in the butchers’ shop such as tables, logs, hooks, weighing balances, aprons and knives and the clothes and hands of butchers. The aim of this research is to assess meat contact surfaces for Salmonella and Shigella species in selected butcher shops in Wukari. Samples were collected randomly using sterile swab sticks from 120 contact surfaces, including 60 samples from School gate, 60 samples from New market and 5 samples from Old market in selected butcher shops in Wukari. The samples were inoculated using the streak plate method onto prepared Salmonella-shigella agar and incubated at 37°C for 24 h. Colonies were sub cultured to obtain pure colonies which were identified using biochemical tests. Antibiotic susceptibility testing was done using the Kirby-Bauer disc-diffusion method after standardizing the inoculum using McFarland standards. The predominant bacterial isolate was Salmonella species (20.8%), while Shigella spp. (16.7%) was the least dominant bacterium. Salmonella spp. was 100% resistant to Ceporex, Augumentin, Peflacine, Ceftazidime. Shigella spp. was 100% resistant to Augumentin, Ceftazidime, Cetriaxone, and Ciprofloxacin. Both species had MRA index greater than 0.2. The results show high bacterial contamination on meat contact surfaces in Wukari, including Salmonella and Shigella, with high antibiotic resistance to commonly used antibiotics. Strict hygiene practices, including regular hand washing, use of gloves, and proper sanitation of meat contact surfaces, should be implemented and enforced.